Pengembangan Pemasaran Digital Berbasis Media Sosial Instagram Untuk Meningkatkan Daya Jual Hasil Produksi Pada Kelompok Tani Urban Farming “Keputih Bersemi” Kelurahan Keputih, Kecamatan Sukolilo, Kota Surabaya - Brilliant Adam Ramadhani; Shalahuddin Fathan; Jessica Putri Margaretta; Putri Wahyu Pebrianti; Ika Sari Tondang; Nuriah Yuliati (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The Urban Farming Group "Keputih Bersemi," based on educational hydroponics, is an active farming group in Kelurahan Keputih, Surabaya. Urban farming is an ideal choice for urban residents to engage in productive activities that can be followed by the surrounding community and, of course, produce something of added value. The plants or vegetables grown by the Keputih Bersemi farming group include pak choi, lettuce, and others. The harvested produce has not been sold or distributed optimally because marketing activities are conducted conventionally, with members offering the products directly to the surrounding community. This situation arises because the majority of the farming group members are elderly and still unfamiliar with technology. The use of social media, such as Instagram and Whatsapp, plays an important role as it significantly increases the visibility and sales of the group's agricultural products. A marketing strategy that involves engaging content, the use of relevant hashtags, and active interaction with potential customers will expand market reach and attract more potential customers.